1975
DOI: 10.1161/01.cir.52.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal left ventricular wall motion at mid-ejection in patients with coronary heart disease.

Abstract: The degree of inward motion at mid-ejection was examined for seven segments on the silhouettes of left ventriculograms taken in the 30°RAO projection in patients with normal coronary arteries. The pattern of wall motion described in these patients was used to distinguish abnormalities in mid-systolic wall motion. WITHIN THE PAST DECADE the more widespread use of left ventricular cineangiography in the study of patients with coronary heart disease has led to descriptions of regional abnormalities of contractile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

1978
1978
1986
1986

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 12 publications
0
9
1
1
Order By: Relevance
“…Leighton et al (1975) found abnormally contracting segments at mid-ejection in 27 out of 42 patients with coronary artery disease. Though ANTERIOR APEX INFERIOR these authors specifically excluded wall movement before aortic valve opening from consideration, it seems likely that regions with properties similar to those of type I were being studied.…”
Section: Discussionmentioning
confidence: 90%
“…Leighton et al (1975) found abnormally contracting segments at mid-ejection in 27 out of 42 patients with coronary artery disease. Though ANTERIOR APEX INFERIOR these authors specifically excluded wall movement before aortic valve opening from consideration, it seems likely that regions with properties similar to those of type I were being studied.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Slutsky et al 12 defined the onset of systole as either the frame preceding the appearance of angiographic dye in the aorta if clearly visualized or else the frame nearest to 0.04 sec after the R wave on the ECG; Leighton et al 10 determined the onset of ejection from the volumetime curve with a computer method and two observers. Our study analyzed many time points, however.…”
Section: Resultsmentioning
confidence: 99%
“…where m'j and m j are averaged patterns m, and rn_j. Cluster separation measure was defined as the ratio between the mean intra-cluster and mean S(c i' (5) where s(c,-, GJ ) is separation of the clusters c{ and GJ , CjCM, CjCM and GJ , CjGC=^c 1 , c2 ,...,c n|.…”
Section: Clustering Of Motion Patternsmentioning
confidence: 99%